2020
DOI: 10.1044/2020_jslhr-19-00296
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Auditory and Somatosensory Feedback to Vocal Motor Control

Abstract: Purpose To better define the contributions of somatosensory and auditory feedback in vocal motor control, a laryngeal perturbation experiment was conducted with and without masking of auditory feedback. Method Eighteen native speakers of English produced a sustained vowel while their larynx was physically and externally displaced on a subset of trials. For the condition with auditory masking, speech-shaped noise was played via earphones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Indeed, the two systems should have reciprocal connections to perform a well-organized process of error detection and correction successfully. A very recent study 43 reached the exact same conclusion. The speech error detection system has a complex nature with many subcomponents involved, and likely under the supervision of shared sensorimotor brain areas responsible for the functional coupling between speech perception and production systems 65 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, the two systems should have reciprocal connections to perform a well-organized process of error detection and correction successfully. A very recent study 43 reached the exact same conclusion. The speech error detection system has a complex nature with many subcomponents involved, and likely under the supervision of shared sensorimotor brain areas responsible for the functional coupling between speech perception and production systems 65 .…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, evidence for a lack of relationship has been reported by Feng et al 40 for the correlation between adaptation to F1 manipulation and auditory acuity for F1, Cai et al 41 for the correlation between speaker’s JNDs toward the F1 manipulation and compensatory responses to F1 manipulations, Abur et al 42 for the correlation between adaptation to F0 manipulation and F0 JND, and most recently, Smith et al 43 for the correlation between compensatory responses to F0 manipulation and F0 JND.…”
Section: Introductionmentioning
confidence: 99%
“…The sensory receptors of the muscles of the glottic level would recover sensations similar to those of a healthy voice due to the restoration of the subglottic pressure during phonation and/or due to the vibro-tactile stimulation due to the contact between the paralyzed vocal fold with the healthy vocal fold. Furthermore, auditory perception of clearer and/or louder sounding voice is restored as a result of this early injection ( Smith et al, 2020 ). Restoring feedbacks could therefore play a role in the peripheral reinnervation process, but it remains unclear how these processes occur.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory feedback may also play a role. The study of Smith et al (2020) , which investigated the effect of disrupting auditory feedback and proprioceptive feedback on the laryngeal compensatory response, concluded that when both sources of feedback were available and the information received by these two perceptual systems was congruent, the compensatory response was greater. Although this study was not conducted in patients with voice disorders, the presence of auditory feedback may potentiate the effect of proprioceptive feedback detected in the voice-related nuclei in the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of auditory and somatosensory feedback signals on speech motor control are frequently probed in isolation, a critical omission given that speech gives rise to multimodal sensory feedback signals which must be evaluated and compared against each other. A recent study by Smith et al [ 9 ] probed the influence of convergent and divergent feedback signals on speech motor control, demonstrating dynamic patterns of adaptive behavior in response to unimodal and multimodal sensory feedback perturbations. However, it remains unclear how these multimodal feedback signals are integrated in the brain and how these integration processes influence sensorimotor activity supporting speech processing [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%